2020
DOI: 10.3390/ijerph17186479
|View full text |Cite
|
Sign up to set email alerts
|

Application of AULA Risk Assessment Tool by Comparison with Other Ergonomic Risk Assessment Tools

Abstract: Agricultural upper limb assessment (AULA), which was developed for evaluating upper limb body postures, was compared with the existing assessment tools such as rapid upper limb assessment (RULA), rapid entire body assessment (REBA), and ovako working posture analysis system (OWAS) based on the results of experts’ assessments of 196 farm tasks in this study. The expert group consisted of ergonomists, industrial medicine experts, and agricultural experts. As a result of the hit rate analysis, the hit rate (avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…Some studies have compared and validated the three techniques simultaneously. Choi et al [ 21 ], and Kong et al [ 26 ] estimated 196 working postures of agricultural tasks with the Agricultural Upper Limb Assessment (AULA), Agricultural Lower Limb Assessment (ALLA), OWAS, RULA, and REBA, and compared the assessment results with the subjective evaluations using a 10-point scale by 16 ergonomic experts. The studies revealed that based on the quadratic weighted ĸ values, the RULA was in ‘moderate’ and ‘good’ agreements depending on the studies (0.599 and 0.627, respectively), whereas the OWAS and REBA were in ‘moderate’ agreement (0.538 [ 21 ] and 0.501 [ 26 ] for OWAS, and 0.578 [ 21 ] and 0.490 [ 26 ] for REBA) with the expert evaluations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies have compared and validated the three techniques simultaneously. Choi et al [ 21 ], and Kong et al [ 26 ] estimated 196 working postures of agricultural tasks with the Agricultural Upper Limb Assessment (AULA), Agricultural Lower Limb Assessment (ALLA), OWAS, RULA, and REBA, and compared the assessment results with the subjective evaluations using a 10-point scale by 16 ergonomic experts. The studies revealed that based on the quadratic weighted ĸ values, the RULA was in ‘moderate’ and ‘good’ agreements depending on the studies (0.599 and 0.627, respectively), whereas the OWAS and REBA were in ‘moderate’ agreement (0.538 [ 21 ] and 0.501 [ 26 ] for OWAS, and 0.578 [ 21 ] and 0.490 [ 26 ] for REBA) with the expert evaluations.…”
Section: Resultsmentioning
confidence: 99%
“…The number of validation studies for the OWAS and RULA (13 and 14, respectively) was higher than that for the REBA (8). The validations are summarized as follows: (1) while nine studies on the OWAS showed affirmative results in viewpoints of correspondence with valid references and association with MSDs [ 21 , 26 , 28 , 84 , 85 , 86 , 87 , 88 , 89 ], four studies reported negative results [ 25 , 30 , 68 , 90 ]; (2) 13 studies (except a study [ 29 ]) for the RULA were affirmative; and (3) seven studies (except one [ 29 ]) for REBA were also affirmative.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the advantages listed, some researchers still raised an issue about the frailty and the limitations among current ergonomic risk assessment methods [56,[60][61][62]. The question about accuracy and consistency in ergonomic risk assessment methods is often discussed academically.…”
Section: Ergonomic Risk Assessmentmentioning
confidence: 99%